2013
DOI: 10.2106/jbjs.l.00211
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Deep Surgical Site Infections After Primary Total Knee Arthroplasty

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
368
5
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(402 citation statements)
references
References 17 publications
17
368
5
12
Order By: Relevance
“…After removal of duplicates and screening, 109 articles were assessed for eligibility. Finally, 12 observational cohort studies [30][31][32][33][34][35][36][37][38][39][40][41] comparing LAF with conventional ventilation in the OR were identified. Most investigators described the ventilation system used in the control group as "conventional (plenum)" or "ordinary" ventilation system, 30,32,36,39,40 while others reported the use of "conventional turbulent ventilation with HEPA-filtered air".…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates and screening, 109 articles were assessed for eligibility. Finally, 12 observational cohort studies [30][31][32][33][34][35][36][37][38][39][40][41] comparing LAF with conventional ventilation in the OR were identified. Most investigators described the ventilation system used in the control group as "conventional (plenum)" or "ordinary" ventilation system, 30,32,36,39,40 while others reported the use of "conventional turbulent ventilation with HEPA-filtered air".…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have suggested that patients with DM undergoing TKA have a higher likelihood of wound complications and surgical site infections than those without DM [5,6,8,18,20,21,28]. Hence, achieving optimal glycemic control in patients with DM is important.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most common and important diseases thought to be associated with an increased risk of perioperative complications among patients undergoing TKA. Previous studies have reported higher rates of infection [8,18,20,21,28], wound complications [5,6], greater risk of deep vein thrombosis [27,29], poorer outcomes [4,13,14,22,25], and higher mortality [2] in patients with DM undergoing TKA compared with patients without DM. Unfortunately, the prevalence of DM among patients undergoing TKA has been steadily increasing [11,15] and orthopaedic surgeons will be faced with a growing number of surgical patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Wound contamination at the time of the procedure is thought to be a cause of early postoperative infections [10,13,17,18]. Recent studies have shown increased wound contamination and infection rates with the use of modern surgical helmet systems compared with conventional gowns, and it has been hypothesized that the positive pressure within a surgical helmet system may potentially underlie the higher rates of wound contamination and infection [7,11,12,18]. The purpose of our study was to determine the amount of particle contamination at the gown-glove interface in several modern surgical helmet systems as well as conventional gowns.…”
Section: Discussionmentioning
confidence: 99%